Distilling Professional Opinion to Gauge Vulnerability of Guam Avifauna to Brown Treesnake Predation - McElderry, Robert M.; Paxton, Eben H.; Nguyen, Andre V.; Siers, Shane R. (Frontiers in Conservation Science, 2021)
The avifauna of Guam was devastated by the introduction of the Brown Treesnake. Restoration will require the eradication or suppression of Brown Treesnakes (BTS) and the reintroduction of native birds. With eradication of the snake unlikely in the near term, and suppression capabilities limited to specific finite areas, key information for reintroductions is how low BTS abundance must be suppressed for each bird to be re-established based on their vulnerability to BTS predation. Here, we estimate vulnerability, which can no longer be measured directly, so we surveyed biologists who are familiar with one or more of seven Guam birds to distill their knowledge and produce quantitative vulnerability estimates. As is typical of birds adapted to islands devoid of predators, respondents judged that our focal species exhibit few predator avoidance and tolerance traits, leaving body size as the prime determinant of vulnerability. Respondent opinion also holds that any behavior that reduces the likelihood of an encounter by BTS, e.g., roosting/nesting in palm crowns, cavity nesting, and in particular urban dwelling, substantially reduces vulnerability. Our results can help inform species-specific decisions about when it may be safe to consider the release of birds on Guam depending on the relative vulnerability of each species to predation by BTS.